Comparison of photorefraction by photoscreener (PlusoptiXA12R) with autorefractometer and cycloplegic retinoscopy in children between 5 and 15 years - S. Kripa (Journal of Clinical Ophthalmology and Research, 2021)
Aim: The aim of the study is to compare the photorefraction values by photoscreener (PlusoptiXA12R, PO) with those of autorefractometer (AR) (TOPCON RM800) and cycloplegic retinoscopy (CR) in children. Methods: It was an observational cross-sectional analytical study with a sample size of 1000 eyes conducted over a duration of one year in a tertiary eye care center. Children in the age group of 5–15 years with refractive error were screened using photoscreener and AR in noncycloplegic state followed by CR. Interclass correlation and agreement were assessed for measurements taken by all three modalities. Sensitivity and specificity were analyzed. P < 0.05 was taken significant for all statistical tests. Positive likelihood ratio, negative likelihood ratio, positive predictive value, and negative predictive value were statistically analyzed. Receiver operative characteristic curve and area under the curve were plotted. Results: Refraction measurements by photoscreener had a strong positive correlation with measurements from CR and AR. Bland-Altman plots depicted the agreement for measurements taken by all three modalities. Sensitivity and specificity of values were high for photoscreener (PlusoptiXA12R) when compared with CR and AR. Conclusion: We conclude that photoscreener is a reliable alternative to AR and CR for detection of refractive error in children between 5 and 15 years of age.